2012
DOI: 10.2147/cia.s35986
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional screening of older home-dwelling Norwegians: a comparison between two instruments

Abstract: BackgroundIt is important to obtain knowledge about the prevalence of nutritional risk and associated factors among older home-dwelling people in order to be able to meet nutritional challenges in this group in the future and to plan appropriate interventions. The aim of this survey was to investigate the prevalence of home-dwelling older people at nutritional risk and to identify associated factors using two different nutritional screening instruments as self-report instruments.MethodsThis study had a cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 48 publications
4
60
0
3
Order By: Relevance
“…A Norwegian community-based study using MNA-screening that included 6033 randomised subjects over the age of 65 found 13.5% of individuals to be at risk. One notable finding being that this risk increased with age (32).…”
Section: Discussionmentioning
confidence: 99%
“…A Norwegian community-based study using MNA-screening that included 6033 randomised subjects over the age of 65 found 13.5% of individuals to be at risk. One notable finding being that this risk increased with age (32).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, older people who are widowed (3) , living alone (2,9) and of advanced age (3,4,8) are especially vulnerable for being at risk for undernutrition.…”
Section: Instrument Testing Nutrition Older People Screening Instrumentmentioning
confidence: 99%
“…Successful actions have been taken in the past 15 years to prevent and treat malnutrition and these have also shown that nutritional care is important (Westergren, Axelsson, et al, 2009;Törmä, Winblad, Cederholm, & Saletti, 2013). Screening of nutritional status and identifying what may be associated with nutritional problems, have proven to be useful interventions in preventing malnutrition Söderhamn, Dale, Sundsli, & Söderhamn, 2012;Söderström et al, 2013). During recent years, new and improved screening methods have been developed.…”
Section: Nutrition Status In the Elderlymentioning
confidence: 99%